KETERAMPILAN MENULIS BAHASA JERMAN SISWA KELAS XI SMAN 2 JOMBANG DENGAN MEDIA VIDEO EASY GERMAN - SATYA CITRA ANJANI, BERLY (LATERNE, 2018)
In German lessons, students not only learn vocabulary and language, but also grammar. Therefore, a medium is needed to develop the writing skills of the students. Are there any difficulties in attributing expressions in German lessons because they differ in writing from other languages? However, there is a learning medium that can overcome the gloominess. Easy German video is an online series that subjects German speakers around the world to authentic language learning materials using audiovisual media. The formulation of this research problem is "What are the results of the writing skills of students SMAN 2 JOMBANG with Easy German video in the class XI semester 2?" This study uses a revised curriculum 2013 and the application Fit Examination Writing (Goethe-Institut) for the creation of evaluation criteria. Writing theory and video theories to analyze the learning outcomes in research data. The result of the research shows that the results of the writing skills of SMAN 2 JOMBANG of the class X! Has increased. Which from the test study 1.2 and 3. That Easy German video can be used to dialogue the class XI semester 2 with the theme of eating and drinking